Implementasi Sistem Ekonomi Islam Dalam Mengentaskan Kemiskinan di Jawa Timur - Muhammad Syahrul Hidayat; Rika Rizki Rohmah; Binti Nur Asiyah (Universitas Islam Nahdlatul Ulama Jepara, 2023)
Poverty alleviation programs in East Java have not been carried out optimally. Its implementation has not been effective due to the suboptimal management of special autonomy funds and the limited social assistance funds in the regional budget. Therefore, other assistance is needed as a driving force in alleviating poverty through zakat, infaq shodaqoh, and waqf adopted from the Islamic economic system. This study used the literature study method and examined the application of the Islamic economic system in improving the welfare of the people of East Java, especially the grassroots. This research was conducted based on statistical data related to poverty and the Gini ratio from Statistics Indonesia (BPS), Regional Budget (APBD), and Zakat, Infaq, Shodaqoh, and Waqf (ZISWAF) funds from Amil Zakat National Agency (BAZNAS) in East Java. The results of this study indicate that the existence of ZISWAF can be a very potential source of additional funds in assisting government programs to accelerate poverty alleviation. There are five strategic steps that can be taken, including mobilizing the Muslim community massively to become muzakki if they can afford it, legitimizing zakat distribution institutions, improving the internal performance of BAZNAS starting from its distribution which is not only social assistance, but in the form of productive assistance, and intensifying the global ZISWAF concept.